A first in human study of SB-743921, a kinesin spindle protein inhibitor, to determine pharmacokinetics, biologic effects and establish a recommended phase II dose - Holen, Kyle D. (2010)
PURPOSE: To determine the maximum-tolerated dose (MTD), dose-limiting toxicity (DLT), safety, pharmacokinetics, and pharmacodynamics of SB-743921 when administered as a 1-h infusion every 21 days to patients with advanced solid tumors or relapsed/refractory lymphoma. METHODS: Patients who failed prior standard therapy or those without any standard options were eligible. Forty-four patients were enrolled using an initial accelerated dose-escalation phase followed by a standard dose-escalation phase. An additional 20 patients were enrolled at the recommended phase II dose to obtain additional safety and pharmacokinetic data. The doses evaluated ranged from 2 to 8 mg/m(2). The pharmacokinetics of SB-743921 was evaluated at 19 time-points over 48 h following during administration during cycle 1. Toxicity was assessed by the NCI Common Terminology Criteria version 3.0. Response evaluation was performed every 6 weeks. RESULTS: The most common and consistent DLT was neutropenia. Other DLTs observed included hypophosphatemia, pulmonary emboli, SVC syndrome, transaminitis, hyponatremia, and hyperbilirubinemia. The MTD of SB-743921 as a 1-h infusion every 21 days was established as 4 mg/m(2). The maximum plasma concentration and area under the plasma concentration time curve appeared to increase proportionally to dose. One durable objective response was seen in a patient with metastatic cholangiocarcinoma who was on treatment 11 months and 6 patients had stable disease for over four cycles. CONCLUSIONS: The recommended phase II dose of SB-743921 on this specific schedule of a 1-h infusion every 3 weeks is 4 mg/m(2). The promising efficacy and lack of severe toxicities in this study warrant the continued development of SB-743921.